(3OjhGf GHf gGfF GdCfOdSjs - (3GHf gGfjA GdCfOdSj , eMeO Hf gGfjA Hf eMeO Hf SYOhf GdCROj GdCfOdSj, CHh GdbGSe,J (B362 (3g` s
(3ChdgG (B:s
(3GdMH MjK GdeYTQ GdCYOGA hGdUHQ MjK GdcdI GdSjQGA s
(3BNQgG (B:s
(3Hd CfJ hMOc YfOj cd CfSi Je TYQ CHj GdbGSe eMeO Hf gGfF GdCfOdSj, hGdMeO ddg Ydi fYeg s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B130 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B12 - (3U (B88s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B3 - (3U (B241 ; (3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B769s
(3eUOQ GbJfGA GdCUd (B:s
(3GdecJHI GdCgdjI HHGQjS (B(3108) s
Keywords: (3GdCOHs